PENGALAMAN BELAJAR LAPANGAN (PBL) I “CERDAS TANPA ASAP ROKOK” DI DESA MORAMO KECAMATAN MORAMO TAHUN 2023 - Saptaputra, Syawal Kamiluddin; Dewi, Sri Tungga; Jafriati, Jafriati; Zainuddin, Asnia (Universitas Halu Oleo, 2023)
Smoke-free areas are the only effective and inexpensive way to protect people from the dangers of secondhand smoke. Smoking is one of the bad habits of society, the number of consumers continues to increase every year. With the emergence of various health problems that plague the community due to smoking, this study aims to provide an understanding to the community about the dangers of smoking, and its impact on health, and encourage healthy living behavior and smoking cessation so that the Moramo village community is smart without cigarette smoke, This research method uses qualitative research methods, with the technique of determining the information using porposive sampling. While data collection techniques include observation and interviews, in fact in the field it is not done, so there are still many people who smoke carelessly. Some of the obstacle factors, namely the lack of socialization, the lack of commitment of policy implementers, the lack of community compliance, and the non-enforcement of predetermined sanction rules. Therefore, there needs to be increased socialization in the Moramo Village community about the importance of the dangers of smoking and the consequences that will be felt.